Extraction of bioactive compounds (mangiferin) from mahkota dewa fruits using subcritical water extraction process - Ummi Najihah, Md Hashim (2016)
Mahkota Dewa or scientifically known as Phaleria Macrocarpa is a popular herbal plant in Indonesia and Malaysia. The bioactive ingredient in this plant process antihistamine, antioxidant, anti-cancer compound. In this work, experimental studies were performed using subcritical water extraction process to extract the bioactive compound namely mangiferin from Mahkota Dewa fruits. The effect of process parameters which are solid to solvent ratios (30, 40, 50, 60, and 70 g/L), temperature (50, 75, 100, 125, 150 °C) and extraction time (3, 4, 5, 6, 7 h) on the extraction yields were investigated. The extraction yields were analysed and characterised using high performance liquid chromatography (HPLC) and 1,1-Diphenyl-2-picryl hydrazyl (DPPH) assay method, respectively. The highest mangiferin yield is 3.2027w/w % were obtained at 60 g/L of solid to solvent ratio, 100 °C of extraction temperature and 5 h of extraction time. The highest of antioxidant activity is 86.5377 % were obtained at 60 g/L of solid to solvent ratio, 125 °C of extraction temperature, 5 h of extraction time. Antioxidant is defined as a substance which significantly delays or inhibits oxidant process. The high value of antioxidant was obtained from the highest value of DPPH since the remaining DPPH in sample acts free radicals were increased in reactivity of unpaired electron and allowed the development of tissues damage in living organisms.